ISOLATION AND PHYSICOCHEMICAL CHARACTERIZATION OF BRUCELLA PHAGES - A. Y. Shaheen; A. A. Sheikh; M. Rabbani; W. Shehzad; Z. Abbas; M. Maqbool (Journal of Animal and Plant Sciences, 2021)
Bovine brucellosis, caused by Brucella abortus, is an economically significant bacterial disease causing enormous economic losses in developing countries. Due to emerging antibacterial resistance in current use of antibiotics and insufficient immunity by WHO recommended vaccine strategies, it is recommended to cull the positive animals to control the disease. In such circumstances, use of host specific bacteriophages could be an alternate option to control the disease. In present study, brucellaphages were isolated from slurry samples (n=50) of livestock farms. Seven samples were found positive in spot method, while two samples gave the positive plaques of pinpoint size (0.5 mm) with round and clear appearance in plaque assay. Isolated brucellaphages (BaP1 and BaP2) did not produce plaques against Staphylococcus aureus, Streptococcus, Bacillus, Escherichia coli, Salmonella, and Pasteurella multocida. Physicochemical characterization revealed that lytic activity of phages was present up to 60oC which started to decrease at 70oC and maximum stability was between 7 to 9 pH. Exposure of sunlight, normal fluorescent and UV light inactivated these phages within 3 hours, 24 hours and 15 minutes, respectively. Phages become inactivated in 15 minutes when treated with Sodium Dodecyl Sulphate, chloroform, Lysozyme, Proteinase K and EDTA, however, no effect of normal saline, Trypsin and RNAse was observed on brucellaphages. In conclusion, the results have laid the foundation to standardize practical applications of brucellaphages after detailed in-vitro and in-vivo experimental evaluations.
Keywords: Brucellosis; Brucella abortus; brucellaphage; plaque assay; physicochemical characterization